Interaksi Interaksi Aplikasi Abu Jerami Padi dan Pupuk P Terhadap Pertumbuhan Mucuna bracteta pada Tanah Latosol - Hadi, Danang; Ismawati, Ike; Bahruslim; Apriyanto, Mulono; Sunaryanto, Hadi (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study aims to determine the interaction of rice straw ash application and P fertilizer on the growth of Mucuna bracteata on latosol soil. The research was conducted at the Experimental Garden of the Faculty of Agriculture, Lancang Kuning University located at Jl. Yos Sudarso KM 8 Rumbai, Pekanbaru, Riau with an altitude of 16 m above sea level. This research was conducted from October to December 2024. This research was conducted experimentally using a 4 x 4 factorial Completely Randomized Design (CRD), which consisted of two factors, namely factor P (Rice Straw Ash) and factor T (P Fertilizer), and each had 3 replicates with a total of 48 polybags. The first factor is rice straw ash with four treatment levels, namely P0 (control), P1 (rice straw ash 5 gr/polybag), P2 (straw ash 10 gr/polybag), P3 (straw ash 15 gr/polybag). The second factor is the application of P fertilizer with four treatment levels, namely P0 (control), T1 (P fertilizer 1 gr/polybag), T2 (P fertilizer 2 gr/polybag), T3 (P fertilizer 3 gr/polybag). The research data were analyzed using ANOVA (Analysis of variance) with a real level of 5%. If there is a real difference, it is continued with Duncan's multiple range test or DMRT (Duncan Multiple Range Test) with a real level of 5%. The results of variance showed a significant interaction between the application of rice straw ash and P fertilizer on the growth of Mucuna bracteata on latosol soil. The combination of 15 g of rice straw ash and 2 g of P fertilizer gave the best effect on the growth of the number of internodes of Mucuna bracteata and soil pH in latosol soil.